The IL-33-ST2 Pathway Contributes to Ventilator-Induced Lung Injury in Septic Mice in a Tidal Volume-Dependent Manner. Issue 3 (September 2019) - Ding, Xibing; Jin, Shuqing; Shao, Zhenzhen; Xu, Li; Yu, Zhuang; Tong, Yao; Chen, Zhixia; Turnquist, Heth; Pitt, Bruce R.; Billiar, Timothy R.; Zhang, Li-Ming; Li, Quan
Abstract : ABSTRACT: Mechanical ventilation (MV) is frequently employed to manage respiratory failure in sepsis patients and is required for the surgical management of intra-abdominal sepsis. The impact of MV varies dramatically depending on tidal volume, with even moderate tidal volume (MTV) ventilation leading to ventilator-induced lung injury, whereas low tidal volume (LTV) ventilation protects against sepsis-induced acute respiratory distress syndrome. Interleukin (IL)-33 is known to contribute to lung injury in sepsis and its release can be induced by mechanical stress. To determine the relationship between the IL-33-suppression of tumorigenicity 2 (ST2) pathway and patterns of lung injury associated with MV in sepsis, mice were subjected to cecal ligation and puncture (CLP) followed 6 h later by either MTV (10 mL/kg) or LTV (6 mL/kg) ventilation for 4 h. MTV and LTV ventilation alone for 4 h had no impact on lung injury. MTV markedly exacerbated lung injury and inflammation, while LTV significantly suppressed these parameters in septic mice. Lung and plasma levels of IL-33 ST2 were significantly elevated by CLP alone at 10 h. MTV caused further and significant increases in IL-33 and sST2 levels, while LTV significantly suppressed levels induced by CLP. Deletion of IL-33 or ST2 prevented the increase in lung injury and inflammation induced by MTV in septic mice, while administration of recombinant IL-33 in the airway reversed the protection seen with LTV. Taken together, these findings implicate the IL-33-ST2 pathway in the pro-inflammatory changes induced by the mechanical ventilation that leads to lung injury in the setting of intra-abdominal sepsis in a tidal volume-dependent manner.